Determinants of Halal Tourism of Setu Babakan Jakarta Based on Global Muslim Travel Index and Importance Performance Analysis - Handayani, Tati; Sufyati HS; Purwanto Widodo; Pusporini; Anggi Angga Resti (Journal of Islamic Economics and Finance Studies, 2024)
Setu Babakan Betawi Cultural Village (PBB) is a betawi-nuanced tourist area developed by the local government of Jakarta and is planned to become a halal tourist destination. This study aims to determine whether the UN Setu Babakan tourist destination implemented Sharia principles as criteria set by the Global Muslim Travel Index (GMTI). To ensure that the analysis results are valid and credible and can be applied by the management of PBB Setu Babakan, research was conducted using primary data with Importance Performance Analysis (IPA). The respondents were tourists at the UN Setu Babakan, Muslim, and over 17 years of age.  The sample consisted of 130 respondents, most of whom were under 20 years of age, high school, and student education. The results showed that according to respondents, services that need to be improved are hotels, SPAs, saunas and massages, travel bureaus and tour guides, many of which are not halal certified, so tourists hesitate to use these services.  These findings are expected to facilitate managers and local governments to develop the right strategy so that visitors to Setu Babakan increase by improving facilities that are lacking.   Perkampungan Budaya Betawi (PBB) Setu Babakan merupakan daerah wisata bernuansa Betawi yang dikembangkan oleh pemerintah daerah Jakarta, yang direncanakan akan menjadi destinasi wisata halal.  Penelitian ini bertujuan untuk mengetahui apakah destinasi wisata PBB Setu Babakan telah benar-benar menerapkan prinsip-prinsip syariah sebagaimana kriteria yang ditetapkan oleh Global Muslim Travel Index (GMTI). Untuk itu menjamin hasil analisis valid, kredibel dan dapat diterapkan oleh fihak manajemen PBB Setu Babakan maka dilakukan penelitian dengan menggunakan data primer, dengan analisis IPA (Importance Performance Analysis). Responden yang diambil adalah wisatawan di PBB Setu Babakan dan beragama Islam dan usia diatas 17 tahun. Sampel terkumpul sebanyak 130 responden, sebagian besar berusia dibawah 20 tahun, pendidikan high school dan student. Hasil penelitian menunjukkan bahwa menurut responden layanan yang perlu diperbaiki adalah hotel, SPA, sauna dan massage, travel bureau dan tour guide banyak yang belum tersertifikasi halal, sehingga wisatawan ragu-ragu untuk menggunakan layanan tersebut. Temuan ini diharapkan dapat memfasilitasi pengelola dan pemerintah setempat untuk membuat strategi yang tepat agar pengunjung setu babakan meningkat dengan memperbaiki fasilitas yang kurang.